Do short-term increases in river and sediment discharge determine the dynamics of coastal mudflat and vegetation in the Yangtze Estuary?. (1st May 2019) - Hu, Meng-Yao; Ge, Zhen-Ming; Li, Ya-Lei; Li, Shi-Hua; Tan, Li-Shan; Xie, Li-Na; Hu, Zhong-Jian; Zhang, Tian-Yu; Li, Xiu-Zhen
Abstract: Sediment loads by large rivers play a crucial role in determining the fate of estuarine and coastal ecosystems. From 2013 to 2017, this study investigated the dynamics of mudflats and marsh pioneering vegetation ( Scirpus species) in the coastal wetland at downstream end of the Yangtze Estuary. The results showed that, even with the historically lowest scale of upstream sediment load, the mudflat accretion (increase in elevation) and vegetation expansion in the marsh frontier still occurred. In the different monitoring sites, the net increases in the mudflat elevation were 24.34–57.51 cm, and the area of the pioneering vegetation increased by 2.18–4.74 times over 5 years. During the 2016–2017 period, with higher water discharges, the rates of mudflat accretion and vegetation colonization were much higher than those in former years. It was declared that a single-year high water discharge could trigger an intensive increase in sediment transport to the coastal region. Relative to water discharge, the year-to-year sediment load recorded upstream (Datong hydrographical gauging station) might not be a suitable indicator to interpret the mudflat and vegetation dynamics in the Yangtze Delta due to the high uncertainty of sediment loading processes along the transportation path. The recent monitoring indicated that positive interaction between vegetation establishment and sedimentary processes probably contribute to a continuous mudflat accretion and vegetation expansion in the mudflat frontier. We also suggest that a short-term substantial impulse in river and sediment discharge highly stimulated the accretion of coastal mudflat and the consequent expansion of marsh vegetation in the Yangtze Estuary.